AN ANALYSIS THE IMPLEMENTATION OF CLOUD BASED ACCOUNTING SYSTEM AT CV ANEKA JAYA BITUNG - Karinda, Aldo; Regista Muntuan, Justicia; Meily Mambu, Michel (Program Studi Magister Manajemen Universitas Advent Indonesia, 2023)
This study aims to analyze the implementation of a cloud based accounting system at CV Aneka Jaya Bitung, before using a cloud based accounting system, the transition process to a cloud based accounting system, and the benefits after implementing a cloud based accounting system in the purchasing and selling business processes. This study uses a qualitative method with the object of research is CV Aneka Jaya Bitung. The data in this study were obtained through interviews, observation and documentation. Interviews were conducted with 5 employees using cloud based accounting systems, in this case the Odoo application. The results of this study indicate that before the implementation of the cloud-based accounting system, problems occurred, including inaccurate recording and a more time-consuming process in both stock recording and transaction recording. In addition, the authors found obstacles during the transition process to a cloud based accounting system such as lack of employee knowledge, lack of employees who handle the transition process, system complexity, network connectivity, missing and piling data. After implementing the cloud based accounting system, the company will benefit from the aspects of performance, information and data, economics, control and security, efficiency, and service.